Drug use and its associated factors among in-school adolescents in Harari region of eastern Ethiopia - Gari Hunduma; Kasiye Shiferaw; Yadeta Dessie; Tesfaye Assebe Yadeta; Biftu Geda; Negussie Deyessa (International Journal of Adolescence and Youth)
This study aimed to determine the magnitude of current drug use and its associated factors among randomly selected 3227 in-school adolescents in eastern Ethiopia using a multistage sampling technique. Data were collected using questionnaires adapted from the Global School-Based Health Survey. The magnitude of current drug use among in-school adolescents was 5.67% (95% CI: 4.92–6.52). Rural residence (AOR = 2.25, 95% CI: 1.43; 3.54), social media use (AOR = 2.53, 95% CI: 1.75; 3.65), being bullied by others at school (AOR = 8.34, 95% CI: 5.67; 12.56), having a father who used drugs (AOR = 2.20, 95% CI: 1.38; 3.39), and having low self-esteem (AOR = 5.83, 95% CI: 2.77; 12.27) were significantly associated with increased odds of current drug use. The magnitude of current drug use is high. The findings highlight that interventions should focus on rural dwellers, social media users, bully victims, adolescents whose fathers use drugs, and adolescents with low self-esteem.